2009
DOI: 10.1021/jm9008604
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Structure−Activity Relationships of Aminopyridine N-Oxides, a Novel Scaffold for the Potent and Selective Inhibition of p38 Mitogen Activated Protein Kinase

Abstract: A novel series of aminopyridine N-oxides were designed, synthesized, and tested for their ability to inhibit p38alpha MAP kinase. Some of these compounds showed a significant reduction in the LPS-induced TNFalpha production in human whole blood. Structure-activity relationship studies revealed that N-oxide oxygen was essential for activity and was probably a determinant factor for a marked selectivity against other related kinases. Compound 45 was identified as a potent and selective p38alpha inhibitor with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“… Inhibition of p38 was measured as described by Lumeras et al ., (2009) and selectivity of AL8697 is further shown in Supporting Information Table S1. …”
Section: Resultsmentioning
confidence: 99%
“… Inhibition of p38 was measured as described by Lumeras et al ., (2009) and selectivity of AL8697 is further shown in Supporting Information Table S1. …”
Section: Resultsmentioning
confidence: 99%
“…2‐Arylpyridin 1‐oxide and 2‐aryl anilide derivatives are the main building blocks of compounds with diverse medicinal properties such as PDE4 inhibitors for the treatment and prevention of stroke, myocardial infarct and cardiovascular inflammatory diseases ( A ), P38 Kinase inhibitors ( B and C ), C‐FMS kinase inhibitors ( D ), treatment of kidney disorders ( E ), and anti‐cancer ( F ) (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, p38 inhibitors administered prior to LPS in vivo are able to block TNF-α secretion [40] suggesting that the above feedback control mechanism would not function in this case. Similarly, the compounds used in this study have been shown to inhibit inflammation and tissue damage in rat adjuvant-arthritis [1,41]. A reasonable explanation for this discrepancy is that the pathways and cell types induced by LPS may be different from those involved in arthritis induction and maintenance, thus highlighting the relevance of the stimulus, the cell types involved and the species in obtaining information that could be predictive of efficacy.…”
Section: Discussionmentioning
confidence: 81%